Antimicrobial Activity of Curcumin against Drug-Resistant Gram-Negative Pathogens in Skin Infections - Gamaryani, Asim; Mukhtar, Muhammad Farhan; Karim Ur Rahman; Iftikhar Ullah; Dur-e-Nayab; Mari Alribi, Abdul Majeed; Taara, Nain; Nisa, Iqbal; Bukhari, Syed Ali (Indus Journal of Bioscience Research, 2025)
Curcumin, a natural polyphenol from Curcuma longa, exhibits significant antimicrobial properties against multidrug-resistant (MDR) Gram-negative bacteria. This study evaluates its efficacy against Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii, common agents in chronic skin infections. The minimum inhibitory concentrations (MICs) of curcumin were determined using broth microdilution, yielding values of 64 µg/mL for P. aeruginosa, 32 µg/mL for K. pneumoniae, and 128 µg/mL for A. baumannii. Checkerboard assays revealed a synergistic effect with ciprofloxacin against P. aeruginosa (FICI = 0.25) and additive effects with ceftazidime and ciprofloxacin against K. pneumoniae (FICI = 0.5) and A. baumannii (FICI = 0.75). Curcumin inhibited biofilm formation and disrupted existing biofilms, reducing biomass by 50% at 32 µg/mL and up to 70% at 128 µg/mL. Reactive oxygen species (ROS) assays showed increasing ROS production correlated with rising curcumin concentrations, suggesting oxidative stress as a key antimicrobial mechanism. Cytotoxicity evaluations on HaCaT cell lines indicated no significant toxicity at concentrations up to 32 µg/mL, with over 80% cell viability. However, viability decreased to 60% at 64 µg/mL and below 50% at 128 µg/mL. These results highlight curcumin’s potential as an adjunctive treatment for MDR bacterial infections due to its antimicrobial activity, biofilm disruption capabilities, and low cytotoxicity at therapeutic doses.